Line spectrum extraction method based on hidden Markov model. Issue 12 (22nd May 2021) - Ma, Kai; Luo, Guangcheng; Cheng, Jian; Cheng, Yusheng; Li, Haitao
Abstract: To solve the difficult problem of line spectrum detection with a low signal‐to‐noise ratio, a line spectrum extraction algorithm based on a hidden Markov model (HMM) is proposed. The forward–backward algorithm was used to track single and multiple spectral lines in a lofargram, and a new algorithm for the state transition probability matrix was proposed to handle the large amount of HMM calculation and the uncertainty difficulty in processing real signals. Finally, a median fitting algorithm was used to correct the few outlier points in the line spectrum estimation process. Simulation and sea trial data showed that the algorithm had good line spectrum tracking ability for a low signal‐to‐noise ratio.